IL-22-expressing murine lymphocytes: Plasticity and pathogenicity - Scott Kenneth Durum (Frontiers in Immunology, 2016)
IL-22 has multiple activities ranging from tissue repair to inflammation. To characterize the pathogenicity and plasticity of cells that produce IL-22 a novel reporter mouse strain was generated. Homeostatic IL-22 reporter expression was observed in intestinal lymphoid cells identified as CD4 T cells and ILC3 cells. In a model of inflammatory bowel disease (IBD), CD4 T cells strongly expressed the IL-22 reporter in mesenteric lymph node. To examine plasticity of IL-22+ T cells, they were purified after generation in vitro or in vivo from inflamed colon, then cultured under Th1, Th2 or Th17 conditions. In vitro-generated IL-22+ CD4 T cells showed relatively durable IL-22 expression under Th1 or Th2 conditions, whereas in vivo generated cells rapidly lost IL-22 expression under these conditions. In vitro-generated cells could not be diverted to express Th1 or Th2 cytokines despite the expression of master regulators. In vivo generated cells could be diverted, at very low frequency, to express Th1 or Th2 cytokines. Both in vitro- and in vivo-generated cells could be induced in vitro to express high levels of IL-17A and IL-17F, assigning them to a Th17 biased class. IL-27 potently downregulated IL-22 expression. To examine IL-22+ T cell pathogenicity, in vitro generated cells were transferred into Rag1-/- mice, retaining modest reporter expression and inducing moderate colitis. In contrast, IL-22 expressers from colitic mice, transferred into secondary hosts, lost reporter expression, acquired high Tbet and modest IFN and IL-17 expression and induced severe colitis. These findings are consistent with a model of strong polarization under optimal in vitro conditions, but a plastic state of T cells in vivo.